2019
DOI: 10.1111/jhn.12711
|View full text |Cite
|
Sign up to set email alerts
|

Does meal‐time insulin dosing based on fat‐protein counting give positive results in postprandial glycaemic profile after a high protein‐fat meal in adolescents with type 1 diabetes: a randomised controlled trial

Abstract: BackgroundThe present study investigated the effects of fat‐protein (CFP) counting in addition to carbohydrate (CARB) counting for calculating prandial insulin dosage on blood glucose profile in patients with type 1 diabetes (T1D) on basal‐bolus insulin therapy.MethodsIn this single centre, cross‐over, randomised, controlled study, control meal (SM: standard meal using a carbohydrate counting method) and three test meals (HPM: high protein meal using a carbohydrate counting method; HPFM‐a: high protein‐fat mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 18 publications
0
45
0
Order By: Relevance
“…The majority of studies were conducted in the clinic (n = 12). 5,[13][14][15][16][17][18][19][20][21][22][23] Seven of the included studies were carried out in adults (>18 years), [13][14][15]17,18,21 one in adolescents (12-18 years), 5 three in children and adolescents (4-17 years), [24][25][26] three in adolescents and adults (13-28 years) 16,20,23 and four in children, adolescents and adults (6-21 years). 19,22,27,28…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies were conducted in the clinic (n = 12). 5,[13][14][15][16][17][18][19][20][21][22][23] Seven of the included studies were carried out in adults (>18 years), [13][14][15]17,18,21 one in adolescents (12-18 years), 5 three in children and adolescents (4-17 years), [24][25][26] three in adolescents and adults (13-28 years) 16,20,23 and four in children, adolescents and adults (6-21 years). 19,22,27,28…”
Section: Study Characteristicsmentioning
confidence: 99%
“…15,29 The remaining three studies included participants only using multiple daily injection (MDI) therapy. 21,23,28 All studies used rapid-acting meal insulin. Twelve of the included studies reported optimising participants' insulin doses prior to starting the study.…”
Section: Insulin Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrates have been accepted as the predominant macronutrient affecting postprandial blood glucose and the major factor for calculating meal‐time insulin doses in type 1 diabetes. Nonetheless, emerging evidence from numerous studies have shown that other dietary factors, including protein, fat and GI, may importantly affect postprandial blood glucose 7,9,21‐24 . Since prandial insulin dose is a major determinant of postprandial glycaemia, choosing the effective insulin algorithm is an important clinical issue 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, new methods to establish a more accurate need of insulin that would consider the complexity of the meal were required. Indeed, some studies showed a better glycemic control when using algorithms for calculating insulin dose that account also for protein and fat intake, besides carbohydrate [ 39 , 40 ]. However, more frequent episodes of hypoglycemia were reported when using supplementary fat/protein counting than CC [ 39 ].…”
Section: Fat Intake and Glycemic Controlmentioning
confidence: 99%